Comparative analysis of post-harvest processing and drying techniques on the cupping quality of Thai Arabica coffee - Sai Aung Moon; Sirirung Wongsakul; Hiroaki Kitazawa; Rattapon Saengrayap (Journal of Agriculture and Food Research)
Climate variability poses significant challenges to Thai Arabica coffee. Unstable weather has negatively impacted the quality of Northern Thai Arabica, leading to issues with quality consistency and reduced market competitiveness for Thai coffee growers. Enhancing refining postharvest processing methods is crucial for improving the overall quality of Thai coffee. This study investigates the impact of drying techniques, i.e., controlled environment drying (CED), sun drying (SD), and fast drying (FD), alongside processing methods. i.e., dry process (DP), washed process (WP), and honey processes (HP), on the pH, total titratable acidity (TA), total soluble solids (TSS), volatile compounds, and cupping scores of roasted coffee beans. Results showed significant differences (p < 0.05) among the drying methods and processing techniques regarding the pH, TA, TSS, volatile compounds, and cupping scores of the roasted beans. CED-DP and CED-HP obtained the highest cupping scores of 83.17 ± 1.26 and 83.33 ± 0.58, respectively. CED gave high levels of total ester and heterocyclic N, FD gave high total acetate, and SD gave high total acid, alcohol, aldehyde, furan, ketone, and pyrazine which link to the sensory attributes. Principal component analysis (PCA) of the chemical compound groups explained 87.97 % of the cumulative variance, revealing distinct associations between processing methods and sensory attributes. DP samples were aligned with acidity, overall, TA, TSS, and total esters and aldehydes, while WP samples were aligned with characteristics such as uniformity, clean cup, acid, alcohol, and pyrazine and HP samples were linked to the sensory characteristics of sweetness, aftertaste, body, flavor, balance, fragrance/aroma, pH, acetate, ketone, furan, and heterocyclic N. These findings offer actionable insights for Thai coffee producers to improve coffee quality by selecting the proper postharvest processing for desired characteristics, despite climatic challenges.